UV-Photokeratitis Associated with Germicidal Lamps Purchased during the COVID-19 Pandemic. (2nd January 2021) - Sengillo, Jesse D.; Kunkler, Anne L.; Medert, Charles; Fowler, Benjamin; Shoji, Marissa; Pirakitikulr, Nathan; Patel, Nimesh; Yannuzzi, Nicolas A.; Verkade, Angela J.; Miller, Darlene; Sliney, David H; Parel, Jean-Marie; et al.
ABSTRACT: Purpose: To report photokeratitis caused by the improper use of germicidal lamps purchased during the COVID-19 pandemic. Methods: Case series. Results: Seven patients presented with acute ocular surface pain after exposure to UV-emitting germicidal lamps. Visual acuity was 20/30 or better in 13 of 14 eyes (93%). Anterior segment examination revealed varying degrees of conjunctival injection and diffusely distributed punctate epithelial erosions (PEEs) in every patient. No intraocular inflammation was identified across the cohort and all fundus examinations were normal. Treatment varied by provider and included artificial tears alone or in combination with antibiotic ointments and/or topical steroids. Five patients were followed via telehealth, one patient returned for an in-office visit, and one patient was lost to follow-up. Five of six patients endorsed complete resolution of symptoms within 2–3 days. Conclusions: Patients should follow manufacturer recommendations when using UV-emitting germicidal lamps and avoid direct exposure to the ocular surface.